PROFESSIONAL COMPETENCE AS A KEY FACTOR IN IMPROVING THE QUALITY OF ENGINEERING EDUCATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The integration of Ukraine into the European community is impossible without changes in the education sphere. The implementation of such projects of the European Union as "Horizon 2020” provides the collaboration between experts in Agriculture and Engineering. The results of the questionnaire conducted by “Agro Survey” agency showed the lack of student’s practical knowledge in Ukrainian Engineering and Agricultural universities. It is obvious that the quality of education in Ukrainian technical universities doesn't meet the requirements of the European labour market. Getting theoretical knowledge has no value until students can apply it for practical purposes. We suggest that a subject like Physics should be practice-oriented. If the Physics course at technical universities integrates theory with practice, students will be better prepared for their future career. The purpose of the study is to define the basic principles of professional competence as the key factor for improving the quality of future engineer’s training in the process of studying Physics. To select and interpret the factual material, concepts and theories the theoretical analysis of philosophical, psychological and pedagogical literature on research was used in the paper. The pedagogical experiment was carried out on the basis of 4 universities in different regions of Ukraine and involved 159 respondents (151 students and 8 university teachers). To determine the strategies for implementation of the profession-based tasks in Physics course we carried out specially designed questionnaires for students majoring in Agrarian Engineering and university teachers. One of the necessary conditions for future engineer training is professional orientation in studying. We suppose that to consider the relationship between a comprehensive Physics course and the disciplines of professional and practical training the in-depth analysis should be performed. First of all, it will help to determine Physics knowledge, abilities and skills that should be used in student’s further professional training. Second of all, it will enable the most effective use of engineering-based tasks in Physics classes. However, knowledge of basic Engineering and General Theoretical subjects is not applied by the students of Technical High School for a long-period of university study. The results of the survey have shown that studying major subjects at a later stage doesn’t motivate students to learn Natural Science and Engineering disciplines. We can conclude that profession-based tasks in Physics class contribute to the formation of a system of natural knowledge, practical skills and abilities. They stimulate the students’ cognitive interest in Physics as a science, help to better absorb material of other disciplines, develop creative abilities and influence the formation of persistent motifs for obtaining knowledge of professional disciplines.